2010
DOI: 10.1002/pmj.20199
|View full text |Cite
|
Sign up to set email alerts
|

Aim, Fire, Aim—Project Planning Styles in Dynamic Environments

Abstract: Ph 61 401991111 (8400 words)Indexing words: dynamism, dynamic, planning, emergent, iterative project management Abstract Rapidly changing environments are a newly recognized and increasing challenge in the field of project management. Traditional prescriptive approaches, orientated around process control, are considered sub-optimal in meeting this challenge. In this article, the authors present an exploratory theorybuilding study aiming to identify the project management approaches used by experienced practiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 15 publications
0
30
0
6
Order By: Relevance
“…This classification was used to study the project management approaches in rapidly changing environments (Collyer et al, 2010). The classification that they propose is used to structure this section: The simplest approach to deal with the challenges of a dynarnic environment is to attempt to make it more static by resisting change.…”
Section: Consequences For Ppm In Dynamic Environmentsmentioning
confidence: 99%
“…This classification was used to study the project management approaches in rapidly changing environments (Collyer et al, 2010). The classification that they propose is used to structure this section: The simplest approach to deal with the challenges of a dynarnic environment is to attempt to make it more static by resisting change.…”
Section: Consequences For Ppm In Dynamic Environmentsmentioning
confidence: 99%
“…Traditional project management methods used for scheduling of construction projects are MS Excel spreadsheets for work planning or MS Project schedules visualizing Gantt charts generated on a Critical Path Method (CPM) basis [15]. In Collyer et al [16], researchers found that traditional project management methodologies have difficulties in dynamic environments due to three major types of changes: (1) project goals; (2) materials, resources tools, and techniques; and (3) relationships with other projects. Therefore, these traditional project management methods are generally not sufficient for the research objectives of this work.…”
Section: State Of the Art And Research Objectivementioning
confidence: 99%
“…Adicionalmente, o foco na qualidade é uma das principais medidas, seguido pelos processos, métodos e ferramentas que são essenciais para o desenvolvimento (FERNANDEZ;FERNANDEZ, 2008;COLLYER et al, 2010). Com a descrição destes aspectos, torna-se possível direcionar as atividades e consequentemente realizar modificações de acordo com a necessidade.…”
Section: Orientações Sobre Gerenciamento De Projetosunclassified
“…Na mesma direção, os aspectos gerais podem ser contabilizados, pois já que os processos, métodos e ferramentas estão presentes, a iniciação pode ser realizada, por conseguinte as análises das possibilidades já podem ser consideradas, bem como o planejamento apresentado de forma adequada (COLLYER et al, 2010;CONFORTO;AMARAL, 2010). A definição desses passos remete diretamente a execução do que foi planejado, com a chance de inclusão de novas ideias que possam colaborar efetivamente com o desenvolvimento.…”
Section: Orientações Sobre Gerenciamento De Projetosunclassified
See 1 more Smart Citation